Marketing efficiency of vegetables in developing economies: Evidences for critical intervention from Rajasthan, India - chand, Khem; kumar, shalander; SURESH, A; DASTAGIRI, M B (The Indian Journal of Agricultural Sciences, 2020)
The purpose of the study is to identify the marketing channels, the relative profitability, and marketing efficiency of vegetables in a developing country, India, and identify points for critical intervention. The study uses field level data collected from farmers who cultivate carrot and tomato. Farm level data was collected from 240 farmers, 60 wholesalers (traders/contractors) and 60 retailers. Farmer’s share in consumer’s rupee is about 25% in carrot and 41% in tomato. The marketing efficiency index in prominent channels of 0.33 in carrot and 0.71 in tomato is quite low. The most common and important constraint is the non-adherence of traders with the prescribed auction system leading to lower price realisation to the farmers, followed by excessive deductions from value realised. Suggestions are provided to enhance marketing efficiency.